CONCEPTS AND FEATURES OF SPECIAL ADMINISTRATIVE AND LEGAL REGIMES IN UKRAINE - Stupak, D. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
The concept and features of special administrative and legal regimes in Ukraine are studied. It is established that special administrative and legal regimes occupy a special place in the system of legal regimes. The peculiarity is that they belong to the field of public safety, national security and national interests, as well as the use of special legal instruments such as granting exclusive powers to public authorities, the possibility of restricting the rights and freedoms of man and citizen and others. It is established that these features include special administrative and legal regimes mostly in the field of administrative law, as the achievement of the goals of their implementation is carried out through the formation of a system of "rigid" public (administrative) management. Researchers' views on the concept of special administrative and legal regimes and their features are studied. It is established that their diversity is justified by the difference in the conditions under which a particular administrative-legal regime is introduced, in particular the purpose of implementation, the type of crisis situation, the subjects of ensuring the implementation of the regimes under consideration, etc. The basic features of special administrative and legal regimes, regardless of their type and conditions of implementation, are highlighted. The author's definition of the special administrative-legal regime as the special order of legal regulation established by administrative-legal norms which is introduced for the purpose of prevention or elimination of threats to national interests and national security with granting to subjects of maintenance of the special legal regime of special powers implementation, measures, including restrictions on human and civil rights and legitimate interests of legal entities within certain space and time limits.
Keywords: legal regime, special administrative-legal regime, concepts, features